2011
DOI: 10.1111/j.1476-5829.2011.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy‐induced myelosuppression in dogs: 103 cases (2002–2006)

Abstract: Definitive radiotherapy refers to delivery of large doses, typically 48-62 Gray, of ionizing radiation over several weeks using a daily or alternate-day fractionation schedule. The impact of definitive radiotherapy alone on haematopoiesis in tumour-bearing dogs is unknown. Medical records from 103 dogs receiving definitive 60 Cobalt teletherapy for cancer over a 5-year period were reviewed for signalment, tumour type and location, total radiotherapy dose and fractionation scheme. Complete blood count data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…These findings are in contrast to the over 33% of cases that showed an increase or worsening in their lymphopenia grade between the two time points. These results are similar to the findings reported in human medicine and the one veterinary study that looked at changes in lymphocyte counts resulting from radiotherapy . There is one veterinary study that looked at changes in CBC values at the midpoint and conclusion of radiotherapy compared to CBC values taken prior to starting radiotherapy.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings are in contrast to the over 33% of cases that showed an increase or worsening in their lymphopenia grade between the two time points. These results are similar to the findings reported in human medicine and the one veterinary study that looked at changes in lymphocyte counts resulting from radiotherapy . There is one veterinary study that looked at changes in CBC values at the midpoint and conclusion of radiotherapy compared to CBC values taken prior to starting radiotherapy.…”
Section: Discussionsupporting
confidence: 87%
“…There is one veterinary study that looked at changes in CBC values at the midpoint and conclusion of radiotherapy compared to CBC values taken prior to starting radiotherapy. They found significant reductions in haematocrit, total white blood cell count, neutrophils, eosinophils, monocytes, lymphocytes and platelets occurred during definitive radiotherapy in 103 dogs . The ALC significantly decreased and the mean lymphocyte count at the end of radiotherapy (0.906 ± 0.65 x 10 3 cell/μL) was below the lower limit of their laboratory's reference interval (1.1 x 10 3 cell/μL).…”
Section: Discussionmentioning
confidence: 97%
“…The incidence of grade 3 or higher leucopenia was significantly greater in the CCRT group than in the chemotherapy-alone group (41.8% versus 24.4%, p = 0.040). It was reported that bone marrow hematopoietic precursors within the radiotherapy field demonstrate an acute radiation injury owing to their rapid and constant proliferative state, resulting in myelosuppression [ 27 ]. The radiation of the ribs, sternum, or thoracic spine may contribute to the greater myelosuppression observed in CCRT.…”
Section: Discussionmentioning
confidence: 99%
“…However, haematological abnormalities have been reported in patients receiving only localised radiotherapy (Clermont et al . ): when standard dose carboplatin was administered concurrently with RT, the frequency of myelosuppression (neutropenia and/or thrombocytopenia) in the combined therapy group was double (21 and 20%, respectively) that in historical cohorts of dogs receiving carboplatin alone (10%) (Page et al . , Rassnick et al .…”
Section: Introductionmentioning
confidence: 99%
“…The dose-limiting toxicities of RT are local effects upon organs at risk. However, haematological abnormalities have been reported in patients receiving only localised radiotherapy (Clermont et al 2012): when standard dose carboplatin was administered concurrently with RT, the frequency of myelosuppression (neutropenia and/or thrombocytopenia) in the combined therapy group was double (21 and 20%, respectively) that in historical cohorts of dogs receiving carboplatin alone (10%) (Page et al 1993, Rassnick et al 2001, Boria et al 2005, Hume et al 2009). Similarly, LeBlanc and colleagues reported unexpected haematological toxicity in dogs with head and neck carcinomas treated with lowdose gemcitabine as a radiosensitiser (LeBlanc et al 2004).…”
Section: Introductionmentioning
confidence: 99%